Control transition mode from voltage control to MPPT for PV generators in isolated DC microgrids - Fernao Pires, Vitor (2022)
The integration of photovoltaic (PV) power sources on a large scale into grid-tied and islanded solutions is now a reality. Despite the fluctuating characteristics of solar energy, the direct current (DC) nature of PV sources is highly compatible with DC microgrids compared with AC solutions. However, as more PV sources are being installed, challenges related to the control of DC microgrids are also increasing, especially for islanded applications. To ensure an appropriate transition from the maximum power point to DC bus voltage regulation of DC microgrids, novel control strategies must be designed, and this aspect is particularly critical when these grids operate without energy storage systems. We therefore propose a new control strategy for a PV generator for islanded DC microgrids without storage systems. Our approach allows for smooth switching from the maximum power point mode to the voltage control regulation mode (V control) when the available PV power is excessive, thus limiting the generated PV power and returning to maximum power point operation when all the available power is required. This allows us to control a DC microgrid without a storage system and provides a new alternative that offers a cost-effective solution for rural and deprived regions. Our solution combines the maximum power point tracking algorithm with a proportional integral compensator for V control and minimises undervoltage/overvoltage problems in the DC bus. The behaviour of the isolated DC microgrid under different conditions, for example in the case of transitions, perturbations, and different types of loads, is also studied and verified. The performance of the proposed control strategy is confirmed by several simulation and experimental tests.